Reglementation generale : Regles et reglements. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy